Correspondence between Breeding Values of the Same Pinus taeda L. Genotypes from Clonal Trials and Half-Sib Seedling Progeny Trials. Issue 5 (10th September 2020) - Shalizi, Mohammad Nasir; Gezan, Salvador Alejandro; McKeand, Steven E; Sherrill, Joshua R; Cumbie, W Patrick; Whetten, Ross W; Isik, Fikret
Abstract: The correspondence between breeding values of 65 loblolly pine ( Pinus taeda L.) genotypes from clonal genetic tests and half-sib seedling progeny tests was studied in the southern United States. The two experiments were established separately, 10 years apart. Additive genetic variance estimates from clonal tests were larger compared with the estimates from the half-sib progeny tests, regardless of the covariance structure used in the statistical models and the traits. However, clone-mean and half-sib family-mean heritability estimates were comparable for all traits, ranging between 0.88 and 0.99. Based on the independent analysis, the correlation between the breeding values of the same genotypes from two propagule types was moderate (0.59) for tree height and stem volume. The combined analysis resulted in a strong genetic correlation (>0.93) between the breeding values of two propagule types. Herein the large discrepancy is mainly the outcome of different data analytical approaches. Conclusively, selecting genotypes for deployment based on clonal testing may not be optimal, but forest tree breeders can use the results from clonal tests to make some informed decisions.